Initial experience with per-rectal endoscopic myotomy for Hirschsprung’s disease: medium and long term outcomes of the first case series of a novel third-space endoscopy procedure - Bapaye, Amol; Dashatwar, Parag; Biradar, Vishnu; Biradar, Shital; Pujari, Rajendra (Endoscopy, 2021)
Introduction Hirschsprung’s disease (HSCR) is congenital aganglionosis affecting the hindgut and presents with constipation. Surgical pull-through is the current standard treatment but causes morbidity. Per-rectal endoscopic myotomy is a novel third-space endoscopy technique for treating short-segment (SS)-HSCR.Methods Retrospective study of SS-HSCR patients diagnosed on history, contrast enema, rectal biopsies, and anorectal manometry, and treated by PREM. The aganglionic segment was mapped before PREM was performed using third-space endoscopy principles. Stool frequency and laxative usage before and after PREM were compared.Results Nine patients (age 7.5 [± 5.2] years; 7 male) underwent PREM during a 4-year period. Mean aganglionic segment length was 6.3 cm, mean procedure time 96.1 minutes, and mean length of hospital stay 2.5 days. Median follow-up was 17 months (range 9–58 months). Stool frequency was 1/4.4 days before vs. 1/1.2 days after PREM (P = 0.0004). Mean laxative usage was 5.4 units of laxative (UL) before vs. 0.4 UL after PREM (P = 0.0002). No laxatives were used by 6/9 patients after PREM. The single adverse effect seen (anal stenosis) was treated with dilatation. Conclusions PREM is a safe and effective minimally invasive procedure to treat SS-HSCR and results in long-term response.